Nanoemulsi Fraksi Daun Pelawan (Tristaniopsis merguensis Griff) Sebagai Antidiabetes - Ary Samsiar; Robby Gus Mahardika; Occa Roanisca (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Diabetes mellitus is an increased level of sugar in the blood and the secretion of glucose in the urine due to metabolic disorders of insulin secretion. Efforts to treat diabetes mellitus can be done with therapy and drugs, but this can cause side effects. Diabetes can also be treated using herbal ingredients from nature. This study aims to determine the potential of pelawan leaves as an antidiabetic in the form of nanoemulsion.The pelawan leaves were extracted with acetone, then partitioned using MeOH solvent: water, again partitioned with ethyl acetate, then partitioned with n-hexane solvent. The nanoemulsion was prepared using a homogenizer at a stirring speed of 8000 rpm for 30 minutes with a composition of 2.5 ml VCO, 10 ml tween 80 and 37.5 ml water. Nanoemulsion from the MeOH: water and ethyl acetate fraction had better characteristics than the n-hexane fraction nanoemulsion. MeOH fraction nanoemulsion: water has a particle size of 123.8 nm, while ethyl acetate has a particle size of 153.9 nm. Meanwhile, the n-hexane nanoemulsion preparation had the characteristics of a larger particle size, namely 361 nm, and had a polydispersity index of 0.625 nm. The antidiabetic test using ethyl acetate fraction can inhibit α-glucosidase by 1.075% at a concentration of 2.5 mg / ml.